EFEK REDUNDANSI: DESAIN PESAN MULTIMEDIA DAN TEORI PEMROSESAN INFORMASI - Pranata, Moeljadi (Institute of Research and Community Outreach - Petra Christian University, 2004)
Delivering text simultaneously in written and spoken form is common in multimedia presentations. Nevertheless%2C the assumption that simultaneous presentations of written and auditory text is beneficial may be erroneous. From a theoretical perspective%2C it is suggested that it persons are required to coordinate and stimultaneously process redundant material are such as written and spoken text%2C an excessive working memory load is generated. Working memory may be overburdened if instruction involves excessive elements of novel information processed simultancously. The common instructional procedure (particularly in multimedia instructional) of presenting identical spoken and written material simultancously may need to be avoided. Abstract in Bahasa Indonesia : Mengirim teks secara simultan dalam bentuk tulisan dan ucapan merupakan hal yang lumrah dalam presentasi-presentasi multimedia. Namun demikian%2C asumsi bahwa presentasi simultan dari teks tulisan dan terucap menguntungkan mungkin berlebihan. Dari perspektif teoritis%2C dinyatakan bahwa jika pelajar diminta untuk mengkoordinasikan dan secara simultan memproses materi yang berlebihan seperti teks tertulis dan terucap%2C dihasilkan muatan memori kerja yang berlebihan. Memori kerja mungkin terlalu dibebani jika instruksi melibatkan elemen-elemen informasi baru yang berlebihan yang diproses secara simultan. Prosedur instruksional umum (khususnya dalam instruksi multimedia) dari menghadirkan material oral dan tertulis secara simultan mungkin harus dihindari. multimedia%2C instructional%2C message design%2C redundant.